2019
DOI: 10.1016/j.neo.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

PRRX1 Regulates Cellular Phenotype Plasticity and Dormancy of Head and Neck Squamous Cell Carcinoma Through miR-642b-3p

Abstract: BACKGROUND: Dormancy is one characteristic of cancer cells to make patients remain asymptomatic before metastasis and relapse, which is closely related to the survival rate of cancer patients, including head and neck squamous cell carcinoma (HNSCC). PRRX1 has previously been implicated in the invasion and metastasis of the epithelial-mesenchymal transition (EMT) process in different types of human carcinoma. However, whether PRRX1 can regulate cancer dormancy and its reactivation, leading to the migration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Expression of the transcription factor PRRX1 as a transcription factor is related to embryonic limb development, vascular differentiation and skeletal muscle development, [30,31] and it has been suggested that transforming growth factor-b and microRNA regulate expression of PRRX1. [3234] However, details are lacking and further analysis is required to uncover the signaling network regulating PRRX1. In this study, we observed that the level of PRRX1 expression was lower in CCRCC tissues than in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the transcription factor PRRX1 as a transcription factor is related to embryonic limb development, vascular differentiation and skeletal muscle development, [30,31] and it has been suggested that transforming growth factor-b and microRNA regulate expression of PRRX1. [3234] However, details are lacking and further analysis is required to uncover the signaling network regulating PRRX1. In this study, we observed that the level of PRRX1 expression was lower in CCRCC tissues than in adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, PRRX1 stimulates translocation of β-catenin into the nucleus upon Wnt pathway activation, thereby inducing c-Myc and consequent EMT of tumor cells 39 . In head and neck squamous cell carcinoma cells, PRRX1 has a synergistic effect with the activated TGF-β1 on the promotion of the migration and invasion of cancer cells, and regulates the phenotypic plasticity and dormancy of tumor cells 40 . These findings suggest that PRRX1 plays divergent roles in different types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In squamous cell carcinoma, PRRX1 expression is evidently negatively correlated with miR-642b-3p, which is downregulated in PRRX1-overexpressed cells. Reinforced expression of miR-642b-3p can reverse the PRRX1-promoted EMT and cell proliferation 40 . In lung cancer, PRRX1 knockdown inhibits the expression of Caspase 3, caspase 9, Apaf-1, and cytochrome C, leading to enhanced anti-apoptotic capacity and resistance to cisplatin in lung cancer cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…One such strategy takes advantage of the fact that TGFβ is synthesized as a latent form that can be activated by binding to specific integrin receptors that are restricted in where and when they perform this function, and that can only activate TGFb1 and 3 (Robertson et al, 2015). Blockade of integrins, that do not affect activation of TGFβ2 homodimers, may be advantageous in avoiding possible outgrowth of dormant metastatic tumor cells that are growth inhibited by TGFβ2 in bone and lymph nodes (Bragado et al, 2013;Jiang et al, 2019;Yumoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%